Time Sharing Algorithm with Dynamic Weighted Harmonic Round Robin - Iraji, Mohammad Saber (Journal of Asian Scientific Research, 2015)
In operating system is an important issue, Allocates processor time to processes, to be fair. We presented in This paper proposed methods to reduce Average waiting time, average response time, Switch Counts process, through the design of a time sharing non-exclusive scheduling algorithm based on the round Robin and determined accurate time quantum . Among the proposed approaches, weight harmonic- dynamic weight and Subtraction Method are achieved better and more accurate results.